Geopolitical storymaking about Tonga and Fiji: How media fooled people to believe Ma’afu wanted Lau - Brown Pulu, Teena (Te Kaharoa, 2014)
<p style="margin: 12px 0px; color: #111111; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 11.2px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: normal; letter-spacing: normal; orphans: 2; text-align: left; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff;">Just when Tongan Democratic Party leader ‘Akilisi Pohiva stumped the public by saying he admired Fiji’s Prime Minister Frank Bainimarama because “he has been able to make things happen and take development to the people,” the Government of Tonga’s Minister for Lands, Lord Ma’afu, came right out of the blue and trumped him (Tonga Daily News, 2014a, 2014b). Ma’afu topped Pohiva at causing public bamboozlement. <p style="margin: 12px 0px; color: #111111; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 11.2px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: normal; letter-spacing: normal; orphans: 2; text-align: left; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff;">By this, Pohiva was the progenitor of Tonga’s thirty year old pro-democracy movement. Why would he over romanticise about the former military commodore Frank Bainimarama, the hard-line originator of Fiji’s third coup to take place in a period of twenty eight years? Pohiva’s swinging politics from democracy in Tonga to an overthrow of democracy in Fiji baffled readers (Naidu, 2014; Graue, 2014). But Ma’afu took centre stage as the show stopper. <p style="margin: 12px 0px; color: #111111; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 11.2px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: normal; letter-spacing: normal; orphans: 2; text-align: left; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff;">Momentarily, people were gobsmacked and did not know what to make of him. Was Tonga’s Minister for Lands and Survey who was a senior noble in the Tu’ivakano cabinet courting mischief or dead serious? Fiji’s permanent secretary for foreign affairs Amena Yauvoli was certain, we “would just have to wait for the Tongan government’s proposal” (Tonga Daily News, 2014a). But as Tongan journalist Kalafi Moala put it, “they will be waiting for a very long time” on that geopolitical front (Moala, 2014). <p style="margin: 12px 0px; color: #111111; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 11.2px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: normal; letter-spacing: normal; orphans: 2; text-align: left; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff;"><span style="color: #111111; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 11.2px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: normal; letter-spacing: normal; orphans: 2; text-align: left; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; display: inline !important; float: none;">This essay explores the geopolitical storymaking about Tonga and Fiji instigated by <em style="color: #111111; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 11.2px; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: normal; letter-spacing: normal; orphans: 2; text-align: left; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff;">Tonga Daily News <span style="color: #111111; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 11.2px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: normal; letter-spacing: normal; orphans: 2; text-align: left; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; display: inline !important; float: none;">publishing online that Lord Ma’afu had said, “In good faith I will propose to the Minister of Foreign Affairs in Fiji that they can have Minerva Reef and we get Lau in return” (Tonga Daily News, 2014a). The very thought of drawing up a new map instantly ignited outrage from Fijian readers. How then, might Tonga and Fiji’s argument over ownership of the Minerva Reefs play out this time around? Could the region’s geopolitical atlas ever be imagined differently when its cartography was permanently cemented to the era of Western European colonial empire? When the media fooled people to believe Lord Ma’afu wanted the Lau Islands for the Minerva Reefs, what did this signal about how news sites can manoeuver shock advertising and manipulate what politicians say to up their ratings?